Gate-controlled MoTe2 homojunction for sub-thermionic subthreshold swing tunnel field-effect transistor. (October 2021) - Duong, Ngoc Thanh; Park, Chulho; Nguyen, Duc Hieu; Nguyen, Phuong Huyen; Tran, Thi Uyen; Park, Dae Young; Lee, Juchan; Nguyen, Duc Anh; Oh, Jong Hyeok; Yu, Yun Seop; Jeong, Mun Seok
Highlights: Subthreshold Swings of 46 mV dec −1 at 300 K achieved in MoTe2 homojunction TFET. A smaller supply voltage of 0.6 V (vs. 0.7 V for Silicon FET) is realized. SS values are significantly lower than that in reported vdWs heterojunction devices. Variations of I60 match well with theoretical tunneling model by WKB approximation. A body factor of m = 0.21 achieved in band-to-band tunneling current branch. Graphical Abstract: ga1 Abstract: A tunnel field-effect transistor (TFET) activated by a quantum band-to-band tunneling mechanism has encouraged the acceleration of nanodevices owing to its capability to beat the thermionic emission limit of a subthreshold swing (SS) (60 mV dec −1 ) in conventional metal-oxide-semiconductor FETs. Despite numerous studies, fabricating a TFET based on two-dimensional materials remain several major concerns due to factors such as a low on–off current ratio, weak air stability, and large hysteresis. Herein, we developed a MoTe2 homojunction-based TFET with bottom metal contacts and a defect-free polymer substrate. The transfer characteristic shows a sub-thermionic minimum SS of 36.4 mV dec −1 and SS average over four decades of 46 mV dec −1 at 300 K, with negligible hysteresis. In particular, a smaller supply voltage of 0.6 V (vs. 0.7 V for Silicon technology) is realized in the TFET. Furthermore, our device exhibits an excellent on/off current ratio of ~10 8, strong air stability for a period of over several months and a sub-Boltzmann limit, body factor of m  = 0.21. This study demonstrates a strategy for a van der Waals heterostructure assembly and describes the considerable progress in TFET research.